Synthesis α-Fe2O3 nanosized by the gel combustion method. - Đại, Lưu Minh; Loan, Nguyễn Thị Tố (Vietnam Journal of Chemistry, 2012)
α-Fe2O3 powder has been synthesised at low temperature (600oC) by the combustion of gel prepared from polyvinyl alcohol (PVA) and iron nitrates. Factors affecting on process synthesis of nanometer oxides α-Fe2O3 including temperature of gel formation, molar ratio of concentration of ion metal and the concentration of polyvinyl alcohol, temperature of calcining on structure and sizes were investigated. The crystalline process and the morphology of oxides particles were considered by X-Ray diffraction (XRD), Scanning Electron Microscopy (SEM). Surface areas of oxides were determined by the BET (Brunaure-Emmet-Teller) method. Further thermal treatment at 400 - 700oC for 2 hours yields the single phase α-Fe2O3. It specific surface area is 35.5 m2/g for Fe2O3.